Use of injectable platelet rich fibrina associated with xenogenous bone graft to promote bone neoformation in dental surgery: an integrative review (Research, Society and Development, 2022)
The aim of the study is to evaluate the use of this biomaterial in dental surgery to promote bone neoformation. From this, a bibliographic research of the integrative literature review type was performed using the search key ("Bone graft" AND Platelet Rich Fibrin AND Injectable)) OR ("Sticky Bone"), in the Web of Science databases, Scopus, Pubmed and BVS, from studies published between 2016 and 2021, being excluded that used platelet aggregates that were not performed i-PRF and autogenous or allogeneic bone grafts. The attenuated results were that injectable Platelet-Rich Fibrin works as a biological activator that increases the amount of growth and improves the quality of the xenogenous graft, and that the union of these biomaterials provided success in bone neoformation in surgeries in different dental specialties. Being inserted in regions of bone defects, areas of maxillary sinus lifting, bone resorption of periapical lesions and as an adjunct in the treatment of periodontitis. Therefore, it was possible to conclude that current studies present favorable results for the application of i-PRF associated with xenograft. However, there is a need for more studies on the benefits of this technique, such as clinical trials, in order to prove its effectiveness.